2017
DOI: 10.1128/mbio.01986-17
|View full text |Cite
|
Sign up to set email alerts
|

Systematic CRISPR-Cas9-Mediated Modifications of Plasmodium yoelii ApiAP2 Genes Reveal Functional Insights into Parasite Development

Abstract: Malaria parasites have a complex life cycle with multiple developmental stages in mosquito and vertebrate hosts, and different developmental stages express unique sets of genes. Unexpectedly, many transcription factors (TFs) commonly found in eukaryotic organisms are absent in malaria parasites; instead, a family of genes encoding proteins similar to the plant Apetala2 (ApiAP2) transcription factors is expanded in the parasites. Several malaria ApiAP2 genes have been shown to play a critical role in parasite d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
122
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
4
3
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(129 citation statements)
references
References 34 publications
7
122
0
Order By: Relevance
“…For instance, in both P. yoelii and P. falciparum , CelTOS, GEST and SPELD were not detected or were only weakly expressed in oocyst sporozoites, but were among the most abundant proteins in salivary gland sporozoites (Table 2, Table S1). Moreover, the presence/absence of cellular regulators such as specific ApiAP2s, histone modifiers, RNA-binding proteins and other proteins (Table S1) agree with previous reports describing how these types of regulation may be used by the sporozoite 32, 40, 48 .…”
Section: Resultssupporting
confidence: 90%
See 1 more Smart Citation
“…For instance, in both P. yoelii and P. falciparum , CelTOS, GEST and SPELD were not detected or were only weakly expressed in oocyst sporozoites, but were among the most abundant proteins in salivary gland sporozoites (Table 2, Table S1). Moreover, the presence/absence of cellular regulators such as specific ApiAP2s, histone modifiers, RNA-binding proteins and other proteins (Table S1) agree with previous reports describing how these types of regulation may be used by the sporozoite 32, 40, 48 .…”
Section: Resultssupporting
confidence: 90%
“…Beyond the previously defined UIS mRNAs, several other transcripts are notable as their protein products are or may be important to the function of salivary gland sporozoites: FAS-II pathway proteins, fatty acid modifiers, plasma membrane transporters, adhesins/surface proteins ( p113 , speld , tlp ), traversal-related proteins ( celtos ), heat shock proteins, and ApiAP2 specific transcription factors ( e.g. py17x_0523100, pf3d7_0420300 ) 4047 . Together, these transcripts encode for proteins that encompass many essential attributes necessary for sporozoite development, transmission, and infectivity.…”
Section: Resultsmentioning
confidence: 99%
“…One critical regulator of sexual commitment is AP2-G, which is a member of the ApiAP2 family of DNA-binding proteins 8,9 . Forward and reverse genetics in P. falciparum, P. berghei, and P. yoelii has demonstrated that AP2-G is a master regulator of gametocytogenesis [8][9][10][11] . Cells that do not express ap2-g will continue asexual development, whereas those that do are able to commit and enter gametocytogenesis.…”
Section: The Malaria Parasitementioning
confidence: 99%
“…More recently, its ortholog in P . yoelii (PY17X_1417400), named AP2‐G3, was reported to be expressed in both sexual and asexual stages and to play a critical role in gametocytogenesis (Zhang et al , ). Here, we report that this transcription factor is female‐specific and essential for the development (thus designated as AP2‐FG).…”
Section: Introductionmentioning
confidence: 99%